2011
DOI: 10.1094/mpmi-05-11-0116
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Symbiosis Limits Foliar Transcriptional Responses to Viral Infection and Favors Long-Term Virus Accumulation

Abstract: Tomato (Solanum lycopersicum) can establish symbiotic interactions with arbuscular mycorrhizal (AM) fungi, and can be infected by several pathogenic viruses. Here, we investigated the impact of mycorrhization by the fungus Glomus mosseae on the Tomato spotted wilt virus (TSWV) infection of tomato plants by transcriptomic and hormones level analyses. In TSWV-infected mycorrhizal plants, the AM fungus root colonization limited virus-induced changes in gene expression in the aerial parts. The virus-responsive upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 86 publications
6
38
1
Order By: Relevance
“…The effect of mycorrhization of Solanum lycopersicum plants on the infection process with tomato spotted wilt virus (TSWV) suggests that mycorrhizae may cause suppression of plant response to viral infection [23]. Mycorrhizal symbiosis was shown to decrease expression of genes activated during viral infection and reduce visual symptoms in long-term [23]. Similarly, in our study growth promotion of virus-infected plants in mycorrhizal symbiosis was observed.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The effect of mycorrhization of Solanum lycopersicum plants on the infection process with tomato spotted wilt virus (TSWV) suggests that mycorrhizae may cause suppression of plant response to viral infection [23]. Mycorrhizal symbiosis was shown to decrease expression of genes activated during viral infection and reduce visual symptoms in long-term [23]. Similarly, in our study growth promotion of virus-infected plants in mycorrhizal symbiosis was observed.…”
Section: Discussionsupporting
confidence: 77%
“…Since in our study the level of H 2 O 2 was tested 10 weeks after plant inoculation, any potential factors contributing to induction of resistance would have already acted. The effect of mycorrhization of Solanum lycopersicum plants on the infection process with tomato spotted wilt virus (TSWV) suggests that mycorrhizae may cause suppression of plant response to viral infection [23]. Mycorrhizal symbiosis was shown to decrease expression of genes activated during viral infection and reduce visual symptoms in long-term [23].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, in addition to playing a key role in developmental processes and in response to abiotic stresses, ABA has been shown to be involved in the interaction between RNA viruses and their host plants. ABA level was observed to increase in tomato shoots infected by Tomato spotted wilt virus [13], [51] and in tobacco leaves systemically infected by TMV [52]; interestingly, treatment with exogenous ABA improved resistance to TMV infection in tobacco [53]. A first relation between ABA and geminivirus infection was observed in Arabidopsis plants inoculated with the curtovirus, Beet severe curly top virus (BSCTV).…”
Section: Discussionmentioning
confidence: 99%
“…Published articles have demonstrated that the systemic effect of pathogen infection on AM formation is quite variable depending on the tripartite pathogen—AM fungus—host plant interaction. For instance, Alternaria solani infection on leaves reduced the symbiosis rate between G. mosseae and tomato roots (Song et al., ), whereas the tomato spotted wilt virus infection on leaves enhanced the percentage of arbuscules within the G. mosseae ‐inoculated areas (Miozzi et al., ). The effect of AMF colonization on host growth also depends on the species‐specific plant–fungus interaction.…”
Section: Discussionmentioning
confidence: 99%